The Effect of Top Management Support on The Effectiveness of Public Sector Internal Audit in Indonesia with Competence and Independence as Intervening Variables - Kanta Rio Saputra; Srihadi Winarningsih; Evita Puspitasari (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2020)
The phenomenon of corruption cases that often occur in local governments and BPK findings related to weaknesses in the internal control system indicates that the internal audit function in local governments is not yet effective. This study aims to examine and measure how much influence the factors that affect the effectiveness of internal audit in the public sector in Indonesia. The results of this study are expected to be used as a consideration for policy making by the Government, which is currently encouraging the improvement of the effectiveness of internal audit in Indonesia. The population in this study were all internal audits of local government in Indonesia. The data collected in this study were 55 internal audits of local government throughout Indonesia. The research was conducted with a quantitative approach using SEM PLS. The results showed that independence and competence had a significant effect on the effectiveness of internal audit and top management support indirectly had a significant effect on the effectiveness of internal audit through competence and independence. However, top management support directly does not have a significant effect on the effectiveness of internal audit. This research also revealed that with the support of top management to the competence and independence of internal audit, it will be able to encourage a more effective internal audit in carrying out its duties and functions.